Evaluation of Oxidative Stress in Testis and Sperm of Rat Following Induced Varicocele - Erfani Majd, Neem; Sadeghi, Niloofar; Tavalaee, Marziyeh; Tabandeh, Mohammad Reza; Nasr- Esfahani, Mohammad Hossein (Urology Journal, 2019)
Purpose: Oxidative stress (OS) plays a central role in the pathophysiology of varicocele (VC), however, comprehensive studies concomitantly assessing semen parameter along with chromatin status, oxidative stress, and enzymatic antioxidants in both testis and sperm are limited. Therefore, this study aims to assess these parameters in varicocelized rats. Materials and Methods: For this study, 30 Wistar rats were randomly divided into three groups: Control group (I); sham-operated group (II) and left varicocele group (III). Left varicocele was induced and two months after surgery, we evaluated sperm parameters, persistent histone, DNA integrity and lipid peroxidation in sperm and also oxidant/antioxidant markers in testis. Results: The results showed that sperm concentration, motility, and normal morphology significantly decreased in varicocele group compared to other groups (P < 0.001). Also, we observed a significant increase in persistent histone and DNA damage of sperm cells in varicocele rats (P < 0.05). In addition, oxidant assessment analysis showed that ROS level was higher in testis tissue and sperm cells from the left varicocele rats compared to the control group (P < 0.05). Conclusion: This results show that varicocele has a negative effect on spermatogenesis and increased oxidative stress and reduce in antioxidant capacity hand in hand lead to the production of sperm with damaged chromatin which reduces the fertility potential and may jeopardize the future health of the progeny.